Paternidade e desemprego: características do envolvimento paterno e aspetos do relacionamento familiar - Souza, Carmen Lúcia Carvalho de (Universidade do Vale do Rio do Sinos, 2008)
This dissertation was conducted to investigate the theme of paternity and unemployment and it is composed of three chapters. The fist chapter presents the research report which sought to verify paternal involvement in a group of unemployed men with school age children, considering socio demographic characteristics, family relationships and fathers´depressive symptoms. The second chapter contains a systematic review article, Contemporary fatherhood- Academic production between 2000 and 2007, which presents the incidence of national and international articles about the theme, indexed in several databases. The third chapter consists of the empirical article and answers to the research project that oriented this work and originated the research report presented in the first chapter. Considering paternal involvement, it was verified level of education was associated to greater father involvement. There was also greater involvement in didactic, affective, social and availability in families in which men received fi
Keywords: depressão; desemprego; envolvimento paterno; paternidade; depression; father involvement; unemployment; fatherhood; Ciências Humanas